Modigliani Meets Minsky: Inequality, Debt, and Financial Fragility in America, 1950-2016 - Alina K. Bartscher; Moritz Kuhn; Moritz Schularick; Ulrike I. Steins (Center for Economic Studies and ifo Institute (CESifo), 2020)
This paper studies the secular increase in U.S. household debt and its relation to growing income inequality and financial fragility. We exploit a new household-level dataset that covers the joint distributions of debt, income, and wealth in the United States over the past seven decades. The data show that increased borrowing by middle-class families with low income growth played a central role in rising indebtedness. Debt-to-income ratios have risen most dramatically for households between the 50th and 90th percentiles of the income distribution. While their income growth was low, middle-class families borrowed against the sizable housing wealth gains from rising home prices. Home equity borrowing accounts for about half of the increase in U.S. household debt between the 1970s and 2007. The resulting debt increase made balance sheets more sensitive to income and house price fluctuations and turned the American middle class into the epicenter of growing financial fragility.
Keywords: E21; E44; D14; D31; 330; household debt; inequality; household portfolios; financial fragility